Persepsi Wisatawan Terhadap Pengembangan Wisata Alam Pendakian Gunung Pundak, Taman Hutan Raya Raden Soerjo: Tourist Perceptions of The Development of Natural Tourism Pundak Mountain Climbing, Taman Hutan Raya Raden Soerjo - Zulfa, Nurya Rufaida; Sucahyo, Clara Ammelia; Agustina, Ana; Supriyadi, Supriyadi; Fatma, Hilda Nuzulul (Jurnal Silva Tropika, 2023)
ABSTRACT   Mount Pundak natural tourism is a mountain climbing tourist attraction located in Taman Hutan Raya Raden Soerjo area. Excavating information related to tourist perceptions needs to be carried out in order to develop the tourist attraction, which in this case is the Mount Pundak tourist attraction. The aim of this research is to determine factors in tourist’s percepstions of the development of the natural tourist attraction climbing Mount Pundak as well as efforts to develop the natural tourist attraction Mount Pundak. The data collection methods used were observation, questionnaires, literature, and documentation. The data measurement technique uses a Likert measurement scale which is used to measure attitudes, opinions, and perceptions of a person or group to find out whether they agree or disagree with the statement or question asked. The results of the research show that visitor perceptions, especially regarding the attractioness of climbing Mount Pundak, reached a score of 125 with an average percentage of 83,3%, which means that the views and natural conditions are still maintained, this ensuring tourist comfort.   Keywords: Perception, tourist, development     ABSTRAK   Wisata alam Gunung Pundak merupakan objek wisata pendakian gunung yang berada di dalam kawasan Taman Hutan Raya Raden Soerjo. Penggalian informasi yang berkaitan dengan persepsi wisatawan perlu dilakukan guna pengembangan objek wisata tersebut, yang dalam hal ini adalah objek wisata Gunung Pundak. Tujuan dari penelitian ini untuk mengetahui faktor persepsi wisatawan terhadap pengembangan objek wisata alam pendakian Gunung pundak serta upaya pengembangan objek wisata alam Gunung Pundak. Metode pengambilan data yang digunakan adalah dengan menggunakan kuesioner, dengan jumlah responden sebanyak 50 orang dipilih secara acak dari pengunjung yang mendatangi lokasi objek wisata. Teknik pengukuran data menggunakan skala pengukuran linkert yang digunakan untuk mengukur sikap, pendapat serta persepsi seseorang atau kelompok untuk mengetahui setuju atau tidak setuju terhadap pernyataan atau pertanyaan yang diajukan. Hasil penelitian menunjukkan bahwa persepsi pengunjung khususnya pada daya tarik pendakian Gunung Pundak mencapai skor 125 dengan rata-rata persentase 83,3% yang berarti bahwa pemandangan dan kondisi alam yang masih terjaga sehingga menjamin kenyamanan wisatawan.   Kata Kunci: Persepsi, wisatawan, pengembangan